Marxism and Migration
XXII, 323 p. 1 illus.
Keywords: “This exciting and thoughtful collection of essays offers a valuable intervention in understanding global migration and the conditions that precipitate it. An urgent and important volume.” —Laleh Khalili, Professor of International Politics, Queen Mary University of London, UK, and author of Sinews of War and Trade: Shipping and Capitalism in the Arabian Peninsula (2020) “This book is a goldmine for everyone interested in migration, border studies, global labor, and capitalism today. This is a book that deserves to be widely read, shared, and discussed by everyone dedicated to understanding our world—and to changing it.” —David McNally, Cullen Distinguished Professor of History & Business, University of Houston, USA, and author of Blood and Money: War, Slavery, Finance, and Empire (2020) This book approaches migration from Marxist feminist, anti-imperialist, and anti-colonial perspectives. The present conditions of transnational migration, best described as a kind of social expulsion, include migrant caravans and detained unaccompanied children in the United States, thousands of migrant deaths at sea, the razing of self-organized refugee camps in Greece, and the massive dispersal of populations within and between countries. Placing patriarchal capitalism, imperialism, racialization, and fundamentalisms at the center of the analysis, Marxism and Migration helps build a more coherent and historically-informed discussion of the conditions of migration, resettlement, and resistance. Drawing upon a range of academic disciplines and diverse geopolitical regions, the book rethinks migrations from the vantage point of class struggle and seeks to ignite a more robust discussion of critical consciousness, racialization, militarization, and solidarity. Genevieve Ritchie is Lecturer in Critical Studies in Equity and Solidarity, New College, University of Toronto. Sara Carpenter is Associate Professor of Educational Policy Studies at the University of Alberta, Canada. Shahrzad Mojab is Professor of Adult Education at the Ontario Institute for Studies in Education, University of Toronto, Canada. .